Application of integrated Traditional Chinese and western medicine nursing for stroke patients (中西医结合护理在脑卒中患者中的应用价值) - MA Chenxue (马晨雪); DENG Ying (邓颖) (中西医结合护理)
Integrated Traditional Chinese and western Medicine nursing is of great importance to the routine management of stroke patients. Integrative nursing intervention helps to improve the recovery of limb function and activity of daily living, relieve negative emotions and alleviate damage of other organs and systems. This paper reviewed studies on the application and evaluation of integrated Traditional Chinese and western Medicine nursing for stroke patients, and provided reference for early recovery of patients after stroke. (中西医结合护理在脑卒中患者的日常护理中有着重要的应用价值, 有利于促进患者肢体功能和生活能力的恢复, 调节负面情绪, 减轻其他系统疾病的损伤。本研究就中西医结合护理在脑卒中患者日常护理中的应用价值进行综述, 旨在为脑卒中患者的早期康复护理提供参考。)